Amorphous NiFe-layered double hydroxides nanosheets for oxygen evolution reaction. (1st October 2020) - Liu, Jiang; Zhou, Jia; Liu, Shuang; Chen, Gui; Wu, Wei; li, Ying; Jin, Pujun; Xu, Chunli
Highlights: Amorphous nife-layered double hydroxides nanosheets is controllably prepared. Amorphous NiFe-LDH has higher catalytic activity than crystalline NiFe-LDH in OER. The overpotential of amorphous NiFe-LDH for OER is 241 mV at 10 mA cm −2 . Amorphous NiFe-LDH has higher electrocatalytic activity than commercial RuO2 . Abstract: The exposed active sites of NiFe layered double hydroxide (NiFe-LDH) for oxygen evolution reaction (OER) are limited by the compact packing of its two-dimensional lamella. In this work, amorphous NiFe-LDH (A-NiFe-LDH) with abundant active sites are synthesized by using Ni(II) nitrilotriacetate complex anion ([NTAN i ] − ) as morphological control agent, which can expose more active sites of NiFe-LDH by controlling crystalline phase and grain size of NiFe-LDH. Structural characterization demonstrates that [NTANi] − is adsorbed on the surface of A-NiFe-LDH and confirms A-NiFe-LDH is amorphous. The electrocatalytic activity of A-NiFe-LDH for OER is much higher than that of both RuO2 and pristine NiFe-LDH. A-NiFe-LDH has low OER overpotential of 241 mV at 10 mV cm −2 and a small Tafel slope of 55 mV dec −1 . The high electrocatalytic activity of A-NiFe-LDH could be attributed to its amorphous structure. Graphical abstract: Image, graphical abstract